Efficacy of Diosmectite (Smecta)® in the Treatment of Acute Watery Diarrhoea in Adults: A Multicentre, Randomized, Double-Blind, Placebo-Controlled, Parallel Group Study. (30th June 2011) - Khediri, Faouzi; Mrad, Abdennebi Ilhem; Azzouz, Moussadek; Doughi, Hedi; Najjar, Taoufik; Mathiex-Fortunet, Hélène; Garnier, Philippe; Cortot, Antoine
Abstract : Background . Although diosmectite has demonstrated efficacy in the treatment of acute watery diarrhoea in children, its efficacy in adults still needs to be assessed. The objective of this study was therefore to assess the efficacy of diosmectite on the time to recovery in adults with acute diarrhoea. Methods . A total of 346 adults with at least three watery stools per day over a period of less than 48 hours were prospectively randomized to diosmectite (6 g tid) or placebo during four days. The primary endpoint was time to diarrhoea recovery. Results . In the intention-to-treat population, median time to recovery was 53.8 hours (range [3.7–167.3]) with diosmectite (n = 166 ) versus 69.0 hours [2.2–165.2] with placebo, (n = 163 ;P = .029 ), which corresponds to a difference of 15.2 hours. Diosmectite was well tolerated. Conclusion . Diosmectite at 6 g tid was well tolerated and reduced the time to recovery of acute watery diarrhoea episode in a clinically relevant manner.